Psychological Predictors of Stakeholders’ Engagement in the Realization of the Vision, Mission, Goals, and Objectives of Cagayan State University - Beatriz G. Clemente (The Bioscan, 2026)
This study explored the psychological predictors of stakeholders' engagement in the realization of the Vision, Mission, Goals, and Objectives (VMGO) of Cagayan State University. It examined stakeholders' lived experiences in understanding, internalizing, and engaging with the University's VMGO and the psychological factors influencing their engagement in the VMGO in relation to their values, beliefs, motivations, and institutional roles. Utilizing a qualitative research design, the data were gathered from purposively selected stakeholders representing administrators, faculty members, administrative staff, and students . The data from open-ended questionnaire were analyzed using thematic analysis. Findings revealed that stakeholder engagement is shaped by interrelated psychological factors such as organizational identification, intrinsic motivation, psychological ownership, value congruence, institutional pride, sense of belonging, and self-efficacy. Participants described the VMGO as a source of purpose, direction, and shared identity that guided their academic, professional, and social responsibilities. Supportive leadership, positive interpersonal relationships, and an inclusive institutional culture emerged as key facilitators of engagement. The study further revealed that stakeholders demonstrated stronger commitment and participation when their personal values and aspirations aligned with those of the institution.